Development of standardized image interpretation for 68Ga-PSMA PET/CT to detect prostate cancer recurrent lesions - Fanti, Stefano; Giesel, Frederik L.; Haberkorn, Uwe (European journal of nuclear medicine and molecular imaging, 2017)
After primary treatment, biochemical relapse (BCR) occurs in a substantial number of patients with prostate cancer (PCa). PET/CT imaging with prostate-specific membrane antigen based tracers (68Ga-PSMA) has shown promising results for BCR patients. However, a standardized image interpretation methodology has yet to be properly agreed. The aim of this study, which was promoted and funded by European Association of Nuclear Medicine (EANM), is to define standardized image interpretation criteria for 68Ga-PSMA PET/CT to detect recurrent PCa lesions in patients treated with primary curative intent therapy (radical prostatectomy or radiotherapy) who presented a biochemical recurrence.
Gesehen am 22.11.2018